Labour Satisfaction of University Lecturers: Current Approaches to Assessment and Prioritization of Factiors - I. Yu. Ilina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes factors of labour satisfaction of university lecturers during modernization of higher education. The goal of the research is to reveal current approaches to estimating labour satisfaction of lecturers and assess importance of different factors in the general system of lecturers’ attitude to their work. Identification and prioritization of factors of labour satisfaction were based on methods of comparative, typological analysis and the Eisenhower matrix. The empiric base of the research was formed by data obtained during monitoring of education sphere economy, which was done by the Higher School of Economics. During the research characteristics of work satisfaction of university lecturers were shown, which were based on the comparison of the most important expectations from work in the university and realized opportunities provided by the work. The system of factors stipulating work satisfaction of university lecturers includes a wide range of characteristics of professional activities that show the most problematic points of the whole system of higher education. A considerable misbalance between expectations and reality is connected with such aspects as stability of wage and employment, professional growth and career, possibility to plan work. The revealed prioritization of factors in labour satisfaction has partly forced nature. Though it is impossible to compensate in full for the absence of satisfaction by payment for work, the process of softening the negative effect of low pay is now being realized at the expense of social importance, possibilities of professional development and self-realization of lecturer at work. The proposed segmentation of lecturers by the level of work satisfaction can be used in the system of in-university management in development of differentiated HR policy in university.